BRITISH POUND, AMERICAN DOLLAR, EURO .. EFFECT OF THE EXCHANGE RATE ON THE RESULT OF THE TRADE ACTIVITY ENTERPRISE IN POLAND (Research Bulletins of the Faculty of Economic Sciences, 2021)
The exchange rate in foreign trade is a factor influencing the functioning of all enterprises involved in international trade. Enterprises, when they start importing goods and services, or when they sell their goods outside the territory of their home country, become direct entities of foreign trade. The issues discussed in the article are focused on determining the importance of the exchange rate in the process of estimating losses on the operating activities of enterprises. The main aim of the article is to assess the importance of the exchange rate in the conduct of business activity on the international market. The main research question was formulated in the form of whether the exchange rate is important for the activities of enterprises and, if so, how the choice of currency affects the level of profitability of international exchange. The empirical study includes a case study of the operating activities of Polish microenterprises on the international market. Information on transactions concluded on international markets was used to determine the profitability level of the international exchange of the enterprise. The source of information on exchange rate fluctuations was the stoq.pl database. The empirical study period covered the years 2015-2019.
Keywords: exchange rate, foreign trade, enterprise